(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2021)
This paper aimed to evaluate crop yield and physical and chemical characteristics of acerola (Malpighia emarginata Sessé & Mociño ex DC) clones grown in the Alta Paulista region, Brazil. The evaluation comprised 7 clones, namely: Olivier, BRS 238-Frutacor, BRS 236-Cereja, BRS 235-Apodi, BRS 237-Roxinha, Okinawa, and Waldy-CATI 30, studied from October 2018 to April 2019. Crop yield was analyzed based on the accumulated production of 12 harvests, with fresh mass expressed in kg fruit·plant-1. Considering the capacity of 30 harvests per plant within the complete cropping period, total fruit mass (in kg fruit·plant-1) and crop yield (in t ha-1) were estimated. Samples were collected from 4 of the 12 harvests in order to determine average fruit mass (g); average fruit size, fruit height/diameter ratio, and pulp yield (%). Regarding fruit pulp, the analysis consisted of quantifying the soluble solids, expressed in degrees Brix, and the technological index (i.e. pulp yield x °Brix/100). The experiment was conducted in a randomized block design, with 7 treatments and 4 repetitions. The obtained data were statistically processed by analysis of variance using the F test, and the means were compared using the Tukey’s test at the 0.05 significance level. The study concluded that, given the soil and weather conditions of the Alta Paulista region, Olivier, Apodi and Frutacor are the clones mainly recommended for the agro-industrial market, being the Olivier cultivar the first option among the three and appearing in a greater proportion in the area of the commercial orchard studied. Regarding the acerola production for fresh consumption, Olivier and Roxinha are the most suitable clones. Olivier stands out for its good fruit yield, adequate physical and chemical characteristics, and easy manual harvesting.